2016
DOI: 10.11599/germs.2016.1100
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections: a retrospective, descriptive study of causative organisms and antimicrobial pattern of samples received for culture, from a tertiary care setting

Abstract: Due to a high level of antimicrobial resistance amongst the pathogens causing UTI in India, it is cautious to advise or modify therapy, as far as possible, after culture and sensitivity testing have been performed. Regional surveillance programs are warranted for the development of national UTI guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
20
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
6
20
3
1
Order By: Relevance
“…The present retrospective study highlights the age and gender-wise distribution of UTI and antibiotic resistance patterns of uropathogens in the pediatric population seeking healthcare services in south India. Similar to others studies (10,12), proportion of affected males was higher in our cohort. Earlier report has suggested that uncircumcised infant boys are more likely to have UTI since microorganisms may develop under the prepuce and enter the urinary tract (13).…”
Section: Discussionsupporting
confidence: 93%
“…The present retrospective study highlights the age and gender-wise distribution of UTI and antibiotic resistance patterns of uropathogens in the pediatric population seeking healthcare services in south India. Similar to others studies (10,12), proportion of affected males was higher in our cohort. Earlier report has suggested that uncircumcised infant boys are more likely to have UTI since microorganisms may develop under the prepuce and enter the urinary tract (13).…”
Section: Discussionsupporting
confidence: 93%
“…and Proteus sp. A lot of authors indicate a very similar bacterial flora (Krygiel et al 2012;Kalal and Nagaraj 2016;Wang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…UTI is a major cause of disease in older men and all age groups of women. The manifestations of UTI may be different from asymptomatic cystitis to pyelonephritis and septicemia [1]. More than 60% of women have experienced UTI, at least once in their lifetime.…”
Section: Introductionmentioning
confidence: 99%